2007
DOI: 10.1007/s10528-007-9079-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differentiation of the Giant Honey Bee (Apis dorsata) in Thailand Analyzed by Mitochondrial Genes and Microsatellites

Abstract: Genetic diversity and population differentiation of the giant honey bee (Apis dorsata) in Thailand were examined. Six PCR-RFLP mitotypes were generated from digestion of the COI-COII, Cytb-tRNA(ser), ATPase6-8, and lrRNA genes with Dra I and Hin fI. Low genetic diversity (h=0.074, pi=0.032%) and a lack of genetic population differentiation between A. dorsata originating from geographically different regions were observed from mtDNA polymorphisms (P > 0.05). In contrast, microsatellite (A14, A24, and A88) polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Studies using microsatellites have been mainly focused on their use as polymorphic markers in population genetics, genetic diversity, or kinship contexts (reviewed in Schlötterer and Pemberton 1998;Goldstein and Schlötterer 1999). This is particularly true in insects, where reports based on SSR molecular variation are abundant (Insuan et al 2007;Agustinos et al 2011;Blondin et al 2013;Manrique-Poyato et al 2013). In recent years, microsatellite genomic analysis has been powered by the development of high throughput next generation sequencing (NGS) technologies, based on massive sequencing approaches which enable a rapid, low-cost, and low time-consuming way to characterize microsatellites (Malausa et al 2011;Iquebal et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using microsatellites have been mainly focused on their use as polymorphic markers in population genetics, genetic diversity, or kinship contexts (reviewed in Schlötterer and Pemberton 1998;Goldstein and Schlötterer 1999). This is particularly true in insects, where reports based on SSR molecular variation are abundant (Insuan et al 2007;Agustinos et al 2011;Blondin et al 2013;Manrique-Poyato et al 2013). In recent years, microsatellite genomic analysis has been powered by the development of high throughput next generation sequencing (NGS) technologies, based on massive sequencing approaches which enable a rapid, low-cost, and low time-consuming way to characterize microsatellites (Malausa et al 2011;Iquebal et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Population structure in the Western honey bee (Apis mellifera L.) has been largely determined by apicultural practices and human transport (Delaney et al, 2009;Whitfield et al, 2006), except for remaining native honey bee populations in Africa and Europe (El-Niweiri and Moritz, 2010;Ruttner, 1988). In contrast, other Apis species are not cultured and bred by humans to the same extent and are expected to reveal a more natural population structure (Insuan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These authors attributed these findings to intense beekeeping activity. In contrast in A. dorsata (Insuan et al, 2007) and in A. cerana (Sihanuntavong et al, 1999) high genetic differentiation was found among populations, probably because of the short-range migration behavior in these bees. In Bombus ignitius, the migration distance is indicated by Shao et al (2004) to be the main factor that drives genetic variation within and among populations.…”
Section: Resultsmentioning
confidence: 75%
“…Estoup et al (1993) found Ho = 0.69 in Apis mellifera, De la Rúa et al (2004) observed an average Ho of 0.45 for Apis mellifera iberica in Spain. Insuan et al (2007) found an index of Ho = 0.71 in Apis dorsata in Thailand. It is known that Apis queens can be fertilized by 15 to 17 males (Adams et al, 1977;Lobo and Kerr, 1993).…”
Section: Resultsmentioning
confidence: 97%